Advancement of Methanol Purity in CO2 Hydrogenation Process Through Design Optimization, Multistage Compression Simulation, and Purification Model Refinement - Verani, Serlyna Maulidya; Azhari, Tanaya Labita; Ridani, Nuraida; Nurardani, Muhammad Romy (Journal of Chemical Engineering Research Progress, 2025)
Rising greenhouse gas emissions, particularly CO2, present significant environmental challenges. The goal of this study is to improve methanol synthesis using CO2 hydrogenation, with an emphasis on increasing purity. To accurately restrict temperature rises during CO2 compression, we did simulations with Aspen HYSYS V11 and a multistage compression approach.  Two notable alterations included the insertion of an absorber unit to improve methanol purity and the recycling of separator outputs. The results show that these process innovations save energy and raw resources while significantly improving methanol output. The findings demonstrate the viability of CO2 hydrogenation as an environmentally beneficial method of producing methanol, which reduces greenhouse gas emissions while still providing a viable chemical feedstock. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).